Beyond tradition : A novel approach for edible bird nest cleaning and its processing - Aizi Nor Mazila, Ramli; Sharifah Zafierah, Syed Badrulzaman; Patil, Reshma Rohit; Nur Izyan, Wan Azelee; Nor Hasmaliana, Abdul Manas; Aimi Wahidah, Aminan (Springer Science and Business Media B.V., 2024)
An edible bird nest is a product of the solidified saliva secretion from a few different swiftlet’s species, during the breeding season. But the high impurities in A. maximus and C. esculent nests make them less ideal to be consumed. Eggshells and guano are the major contaminants contributing to the nitrite and nitrates contents. However, recent studies have shown significant medicinal and cosmetic applications of edible bird nest like anti-viral, anti-inflammatory, enhancing bone strength, and anti-aging. Thus, the high demand for edible bird nest in the global market to explore its potential application has improved from swiftlet farming activities to the cleaning process. Recent studies have shown the use of immobilized enzymes like keratinase for the removal of contaminants. The current review discusses the importance of Swiftlet bird nest, its application, and commercialization.